2023
DOI: 10.7717/peerj.15817
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of technical characteristics of typical lower limb balance movements in Tai Chi: a cross-sectional study based on AnyBody bone muscle modeling

Abstract: Background Tai Chi is an excellent traditional Chinese physical fitness exercise, and its unique balancing movements are very important for improving human balance. In this study, the two most representative Tai Chi balance movements, “knee lift balance” and “leg stirrup balance”, were selected to establish the lower limb bone muscle model of Tai Chi balance movements by using computer simulation modeling technology, aiming to analyze the characteristics of the lower limb movement mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Badminton smash is a common scoring technique 43 , and understanding of the effect of fatigue on the biomechanical parameters of ankle joint during smash landing actions is crucial to obtaining insights into its biomechanical effects during single-leg landing. Previous studies have revealed the negative effect of fatigue on single-leg landing actions in smashes 31 , 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Badminton smash is a common scoring technique 43 , and understanding of the effect of fatigue on the biomechanical parameters of ankle joint during smash landing actions is crucial to obtaining insights into its biomechanical effects during single-leg landing. Previous studies have revealed the negative effect of fatigue on single-leg landing actions in smashes 31 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Musculoskeletal simulation models for BRJS and BLJS were established. The computational process was conducted in the following this sequence: reflective marker optimization, dynamic calculation, and inverse dynamics analysis 43 .…”
Section: Methodsmentioning
confidence: 99%
“…This muscle behavior, in passive and active scenarios, marked by a certain deformability between elongation and shortening, corresponds to information about relaxation and contraction, which is difficult to measure in practice, especially during complex movements. Physical and computerized muscle models have been developed for measuring muscle length and moment arms in healthy individuals [95][96][97][98]. Figure 5 demonstrate an example of a biomechanical analysis of the muscles in the upper limb using the Newcastle shoulder model [99].…”
Section: Soft Tissuesmentioning
confidence: 99%